New finds of Roman provincial coins in Belarus - Sidarovich, Vital (Acta Archaeologica Lodziensia, 2024)
The article presents data on new finds of Roman provincial coins in Belarus, which were obtained in 2014-2024, and discusses all currently known finds, among which coins from the Balkan provinces, mainly from Thrace. In Belarus, four main areas of occurrence of Roman provincial coins have been indicated. It was found that these coins were the most characteristic for regions that were in the Kyiv culture zone during the Roman period, while in the Wielbark culture zone they are quite rare